Development of a Long Jump Learning Model with Varied Hurdle Jumping Activities - Indah Yuliantika; Meirizal Usra; Wahyu Indra Bayu; Hartati Hartati; Syafaruddin Syafaruddin; Herri Yusfi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research aims to produce a long jump learning model with varied hurdle jumping activities at the YP Indra Plaju Elementary School. The type of research used is research and development (R&D), which is research to produce a product in the form of a long jump learning model with varied hurdle jumping activities. The population of this research was 30 YP Indra Plaju Elementary School students. The sampling technique in this research is for small group testing of 10 students and for large group testing of 20 students. The data collection techniques used are product validity, interviews, observations, filling out questionnaires with students. The instruments in this research are validation sheets and questionnaires. The data analysis technique is validity analysis, practicality analysis and effectiveness analysis. Based on the research results, the results of the validator assessment with revisions and suggestions obtained an average of 4.3 in the feasible and usable category. From the limited scale test questionnaire, the average score was 4.45 with adequate criteria. The large scale test obtained a score of 4.6 which is at a good level and suitable for use. The effectiveness and interest of long jump learning materials with hurdle jumping activities varies in elementary schools according to the research results. It is very effective, according to the research results, the value obtained is 5. Based on the assessment criteria, a score of 5 is in the very effective category. This means that the long jump lesson material with varied hurdle jumping activities is very effective for learning the sport of long jump at school. The conclusion of this research is that the long jump learning model with varied hurdle jumping activities can be declared valid in its use and this learning model is practical to use and this learning model is effectively used to support long jump learning activities. The implementation of the results of this research is that the long jump learning model can be carried out with varied hurdle jumping activities.